2019
DOI: 10.15436/2377-0619.19.1994
|View full text |Cite
|
Sign up to set email alerts
|

Honey as Versatile Remedy: A Focus on Selected Honeys

Abstract: Introduction: Honey is one of the oldest traditional medicines. It has been well known that honey contains various components that could be use as treatment option. Most commonly studied honeys include gelam, kelulut, acacia, tualang and pineapple honeys. This review listed the five most commonly studied honeys, its properties and the study model involved.Results: Honey has been reported to have multiple properties. Honeys were used to study their antimicrobial properties which includes antibacterial and antif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 83 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…is the bee species involved in the production of KH. Derived from multiflora sources, KH was reported to be ten times higher in antioxidant properties [ 9 , 10 ]. Reports from the previous studies showed that the total phenolic content (TPC) of the KH was higher compared to New Zealand manuka honey [ 9 , 10 ] and the total flavonoid content (TFC) was higher from Portuguese heather honey and Spanish rosemary honey [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…is the bee species involved in the production of KH. Derived from multiflora sources, KH was reported to be ten times higher in antioxidant properties [ 9 , 10 ]. Reports from the previous studies showed that the total phenolic content (TPC) of the KH was higher compared to New Zealand manuka honey [ 9 , 10 ] and the total flavonoid content (TFC) was higher from Portuguese heather honey and Spanish rosemary honey [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Derived from multiflora sources, KH was reported to be ten times higher in antioxidant properties [ 9 , 10 ]. Reports from the previous studies showed that the total phenolic content (TPC) of the KH was higher compared to New Zealand manuka honey [ 9 , 10 ] and the total flavonoid content (TFC) was higher from Portuguese heather honey and Spanish rosemary honey [ 10 , 11 ]. Additionally, ferric-reducing antioxidant potential (FRAP) assay showed that the antioxidant activity of KH was higher than that was found in New Zealand manuka honey [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Malaysia, there are several types of honey including tualang, gelam, nenas, acacia and kelulut honey. Honey possesses anticancer, antibacterial, antimicrobial, anti-ulcer, anti-inflammatory, antinociceptive and antioxidant properties apart from being able to heal wounds and being a potential adjuvant (Hassan & Abdul Karim 2018;Machado De-Melo et al 2018;; Putri Shuhaili et al (Hassan & Abdul Karim 2018) which are essential for health and wellbeing of the host (LeBlanc et al 2017;Mohan et al 2017) For example, gelam honey contains high level of phenols, proteins, vitamins and amino acid which contribute to its anticancer and antioxidant properties (Goon et al 2017). Manuka honey also shows antioxidant property as it attenuates H 2 O 2 -induced oxidative stress in human whole blood cell (Zivkovic et al 2018).…”
Section: Introductionmentioning
confidence: 99%